Providing Care by Telephone to Refugees and Asylum Seekers: An Evaluation of Telephone Mode-of-Care in Monash Health Refugee Health and Wellbeing Clinic in Victoria, Australia. (November 2022) - Kunin, Marina; Ali, Razia; Yugusuk, Chris; Davis, Annette; McBride, Jacquie
An evaluation of accessibility, appropriateness, acceptability and efficiency of telephone consultations, implemented at Monash Health Refugee Health and Wellbeing (MH RHW) throughout the COVID-19 pandemic, was conducted. A convergent mix-methods design was used, with both patients (n = 50) and clinicians (n = 11) participating in a survey, and two focus groups (n = 14) involving clinicians being conducted. Service utilization data was sourced from the MH RHW database. During May to December 2020, 61% (n = 3012) of the consultations were conducted by telephone, 42% (n = 11) of these required interpreters in a 3-way conversation Most patients were satisfied with telephone as a medium for providing care and with the quality of telephone-based care. Similarly, clinicians considered telephone consultations to be an acceptable mode-of-care for most patients during the pandemic, however, expressed caution in relation to certain patient cohort. Finally, the provision of care by telephone was considered no more efficient than face-to-face service provision, as reflected in the time required for each consultation, with some clinicians reporting adverse workload outcomes. This study highlighted the benefits and challenges of telephone consultations from patient and clinician perspectives. It also highlighted the types of patients that may not be suited to telephone consultations. Overall, this study showed that telephone service delivery is a feasible option in providing care to people of refugee background and should be considered in future decisions as an ongoing Medicare (Australia's universal healthcare insurance scheme) billing item. However, clinical discretion should prevail in determining the most appropriate means of delivering care.